2020
DOI: 10.9755/ejfa.2020.v32.i5.2107
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographic analysis of the fatty acid composition of mustard oil obtained by cold pressing (method)

Abstract: Nowadays there is such a type of product as mustard oil, which is a stockpot of valuable fatty acids and vitamins. Mustard oil is used in various fields of industry. It has a characteristic smell and taste, yellow-brown color. Mustard grows mostly in the southern regions. It is resistant to various diseases and pests. There is evidence from scientific research that proves the beneficial properties of this oilseed. Mustard oil was obtained by cold pressing under the following conditions: annular gap of the grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…The FAs compositions revealed in this article demonstrate quantitative correlations with an investigation by Schwarzinger et al [86]. Interestingly, the mustard oil obtained by the cold press method showed that the oleic acid was the major component, whereas the erucic acid was a minor component [87,88]. However, differences in genotype, edaphic variables, pedo-climatic conditions, harvest time, extraction procedure, and analytical procedures can all contribute to variations in the FA composition of mustard oil [89].…”
Section: Gc-ms Analysissupporting
confidence: 69%
“…The FAs compositions revealed in this article demonstrate quantitative correlations with an investigation by Schwarzinger et al [86]. Interestingly, the mustard oil obtained by the cold press method showed that the oleic acid was the major component, whereas the erucic acid was a minor component [87,88]. However, differences in genotype, edaphic variables, pedo-climatic conditions, harvest time, extraction procedure, and analytical procedures can all contribute to variations in the FA composition of mustard oil [89].…”
Section: Gc-ms Analysissupporting
confidence: 69%
“…When crushed, these compounds transform into isothiocyanates and thiocyanates, lending mustard oil its sharp flavor and potential health benefits. Mustard oil's characteristics vary due to factors like plant type and processing methods, making it a common ingredient in South Asian and Mediterranean cuisines, but it should be used in moderation [149].…”
Section: Mustard Seedsmentioning
confidence: 99%
“…Это поведение можно объяснить постепенным вращением и ориентацией макромолекул в направлении потока. Увеличение содержания влаги и температуры (тепловой энергии) увеличивает подвижность белковых молекул для вращения, поэтому растворы проявляют меньшее поведение, зависящее от сдвига [6,7].…”
Section: результаты и обсужденияunclassified
“…В жидкостях молекулы тесно упакованы вместе, межмолекулярные силы доминируют и пытаются противостоять напряжениям сдвига, возникающим, когда жидкость вынуждена двигаться. С повышением температуры степень молекулярного движения увеличивается, уменьшая силы притяжения на малых расстояниях между молекулами и снижая вязкость [7].…”
Section: результаты и обсужденияunclassified